Eosinophilia in school-going children with Plasmodium falciparum and helminth infections in the Volta Region of Ghana - Orish, Verner Ndudiri (Pan Afr Med J, 2021)
INTRODUCTION: eosinophilia is seen in children infected with parasitic organisms. This study aimed at evaluating eosinophilia in children infected with Plasmodium falciparum, Schistosoma haematobium and intestinal helminths in the Volta Region of Ghana. METHODS: five hundred and fifty primary school children were selected for this study from 5 primary schools in 2 districts and a municipal area of the Volta Region of Ghana. Blood, stool and urine samples were obtained and screened for P. falciparum, intestinal helminths and S. haematobium respectively. Socio-demographic information were obtained using a standardized questionnaire administration. Pearson chi square analysis was used to evaluate the association between eosinophilia and parasitic infections, and multivariate logistics regression analysis was used to identify factors independently associated with increased risk of eosinophilia. RESULTS: a total of 145(26.36%) children had eosinophilia of which 107(73.79%) were infected with P. falciparum infection, (p=0.016); 18(12.41%) with S. haematobium infection, (p=0.016); and 3(2.07%) children were infected with intestinal helminth, (p=0.36). Children infected with P. falciparum had 2 times increased risk of eosinophilia (AOR=2.01, 95% CI, [1.29-3.2], p=0.02); while children from Davanu primary school had 4 times increased risk of eosinophilia (AOR=4.3, 95% [2.41-10.10], p<0.001). CONCLUSION: there was significantly high prevalence of eosinophilia among children infected with P. falciparum infection. A longitudinal study is needed to further understand the immune response of these children to parasitic infections.